Changes in synaptic density in the subacute phase after ischemic stroke: A 11C-UCB-J PET/MR study. Issue 2 (February 2022) - Michiels, Laura; Mertens, Nathalie; Thijs, Liselot; Radwan, Ahmed; Sunaert, Stefan; Vandenbulcke, Mathieu; Verheyden, Geert; Koole, Michel; Van Laere, Koen; Lemmens, Robin
Functional alterations after ischemic stroke have been described with Magnetic Resonance Imaging (MRI) and perfusion Positron Emission Tomography (PET), but no data on in vivo synaptic changes exist. Recently, imaging of synaptic density became available by targeting synaptic vesicle protein 2 A, a protein ubiquitously expressed in all presynaptic nerve terminals. We hypothesized that in subacute ischemic stroke loss of synaptic density can be evaluated with 11 C-UCB-J PET in the ischemic tissue and that alterations in synaptic density can be present in brain regions beyond the ischemic core. We recruited ischemic stroke patients to undergo 11 C-UCB-J PET/MR imaging 21 ± 8 days after stroke onset to investigate regional 11 C-UCB-J SUVR (standardized uptake value ratio). There was a decrease (but residual signal) of 11 C-UCB-J SUVR within the lesion of 16 stroke patients compared to 40 healthy controls (ratiolesion/controls = 0.67 ± 0.28, p = 0.00023). Moreover, 11 C-UCB-J SUVR was lower in the non-lesioned tissue of the affected hemisphere compared to the unaffected hemisphere (ΔSUVR = −0.17, p = 0.0035). The contralesional cerebellar hemisphere showed a lower 11 C-UCB-J SUVR compared to the ipsilesional cerebellar hemisphere (ΔSUVR = −0.14, p = 0.0048). In 8 out of 16 patients, the asymmetry index suggested crossed cerebellar diaschisis. Future research is required to longitudinally study these changes in synaptic density and their association with outcome.